Sensor technologies for civil infrastructures : volume 1: sensing hardware and data collection methods for performance assessment - Lynch, Jerome P. (Jerome Peter); Sohn, Hoon, editor; Wang, Ming L., editor (Cambridge [U.K.] ; Waltham, Mass. : Woodhead Publishing, 2014)
Includes bibliographical references and index